El Anambé Verdoso (Pachyramphus viridis) en el sur de Entre Ríos - Adelqui Brunetti; Mouchard, Alejandro; Coulon, Clotaire; Haene, Eduardo (Nuestras Aves, 1991)
Este artículo no cuenta con un resumen.